2005
DOI: 10.1111/j.0105-1873.2005.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative patch and repeated open application testing in methyldibromo glutaronitrile‐sensitive patients

Abstract: Contact allergy to methyldibromo glutaronitrile (MDBGN), often combined with phenoxyethanol (PE) (e.g., Euxyl K 400), increased throughout the 1990s in Europe. Consequently, in 2003, the European Commission banned its use in leave-on products, where its use concentration was considered too high and the non-sensitizing use concentration as yet unknown. The 2 objectives of the study are (a) to find a maximum non-eliciting concentration in a leave-on product in MDBGN/PE-sensitized patients, which could possibly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…Among the biocides, MDBGN ranks as a top allergen. Together with other evidence (15, 16), its ban in leave‐on products is thus well substantiated. However, also in rinse‐off product (BS‐) positive patients, a significantly elevated proportion of MDBGN sensitized can be noted.…”
Section: Discussionmentioning
confidence: 62%
“…Among the biocides, MDBGN ranks as a top allergen. Together with other evidence (15, 16), its ban in leave‐on products is thus well substantiated. However, also in rinse‐off product (BS‐) positive patients, a significantly elevated proportion of MDBGN sensitized can be noted.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed it has been shown that following repeated applications of radiolabelled PPD to rat skin, followed by washing off (as would occur in the use of a hair dye), there is progressive accumulation of PPD 9 . In addition, when allergic individuals were tested with methyldibromoglutaronitrile in a ROAT at 50 parts per million (0·005%), positive responses were obtained in a third of the allergic subjects 10 …”
Section: Discussionmentioning
confidence: 99%
“…There are clear data that potent sensitizers such as DNCB or diphencyprone can induce a dose‐dependent augmentation in reactivity after high‐dose exposure; for example after application of high sensitizing doses (142 μg cm −2 ) individuals will give positive responses to challenges with as little as 0·8 μg of DNCB 1,2 . However, ingredients in personal products such as fragrances (oak moss) or antimicrobials, mostly regarded as weak sensitizers, are present at low concentrations (< 0·1%) but can induce what has been called very strong sensitization 10–12 . There has been a debate as to whether this indicates that these compounds are actually potent sensitizers or whether repeated exposure to low concentrations somehow potentiates their sensitizing potency 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequency of these reactions is not an accurate indication of the frequency of incidents in which geraniol has been established as the direct cause of contact dermatitis resulting from the use of consumer products and other everyday environmental contact. A recent publication [107] relative to the testing of methyldibromo-glutaronitrile-sensitive patients has discussed another aspect of patch testing. The use of patch-test concentrations that are too high (as the current levels used for geraniol may well be) decreases specifi city without greatly affecting sensitivity.…”
Section: Discussionmentioning
confidence: 99%